Peningkatan keterampilan menyelesaikan soal cerita matematika menggunakan model pembelajaran pair checks pada peserta didik kelas III sekolah dasar - Widiyastuti, Isna; Riyadi, Riyadi; Mulyono, Hadi (Universitas Sebelas Maret, 2020)
Abstract. The goal of this research is improve skill to solve math story problems using Pair Checks learning model. This research is Classroom Action Research with two cycles. The subjects research were students of class III at SDN Mangkuyudan No. 02 Surakarta in the 2019/2020 academic years. Data collection techniques uses observations, interviews, tests, and documentations. Data validity techniques use triangulation, namely triangulation of source data and triangulation of techniques. Data analysis techniques uses interactive descriptive analysis. Results of research on pre-action shows conditions of skill to solve math story problems 0% classically. The first cycle increases to 56% in classical and in the 2nd cycle, increases to 94% in classical. Based on the result of research Pair Checks learning model can be improve skill to solve math story problems students of class III at SDN Mangkyudan No. 02 in the 2019/2020 academic year. This research can be used as a reference for similar research.Keywords: skill to solve math story problems, Pair Checks learning model, primary education